2022
DOI: 10.1039/d2em00034b
|View full text |Cite
|
Sign up to set email alerts
|

Towards improved characterization of the fate and impact of hydraulic fracturing chemicals to better secure regional water quality

Abstract: New approaches to better characterize chemical contamination from hydraulic fracturing of shale and other permeable rock formations for improved risk-based management are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Mitigation measures for such impacts include return-flow fluid management, which involves the proper handling of return-flow fluids containing potentially contaminating chemicals and materials. Research suggests that reusing and treating these fluids can reduce the risk of water contamination [137][138][139][140][141][142]. Additionally, well monitoring, which entails the rigorous monitoring of wells before, during, and after the fracking operation, can help identify and prevent potential leaks and contamination [143][144][145][146][147].…”
Section: Resultsmentioning
confidence: 99%
“…Mitigation measures for such impacts include return-flow fluid management, which involves the proper handling of return-flow fluids containing potentially contaminating chemicals and materials. Research suggests that reusing and treating these fluids can reduce the risk of water contamination [137][138][139][140][141][142]. Additionally, well monitoring, which entails the rigorous monitoring of wells before, during, and after the fracking operation, can help identify and prevent potential leaks and contamination [143][144][145][146][147].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the advancements of horizontal drilling and hydraulic fracturing technologies have promoted the extraction of shale gas. However, shale gas exploration raised concerns on regional water resources due to the usage of large amounts of water and synthetic chemicals for drilling and hydraulic fracturing. As an essential part of the drilling operation, the drilling fluids contain various organic and inorganic compounds from the solid phase, liquid phase, and chemical treatment agent. , Due to reliable shale inhibition and excellent lubricity, oil-based drilling fluids are an essential component in shale gas exploration. , However, oil-based drilling fluids were often considered to be environmentally hazardous due to their high toxicity . Accidental well leakage might release chemicals in the drilling fluids and later contaminate groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies ,, have focused on risks and hazards of hydraulic fracturing fluids and flowback fluids. For instance, Huang et al identified PMT/vPvM substances present in the flowback and produced water (FPW) from hydraulic fracturing of shale gas production .…”
Section: Introductionmentioning
confidence: 99%
“…It plays a role in supporting the roof when working underground and maintaining the safe working space for the mining face. Therefore, the stability and reliability of the hydraulic support is an important factor to ensure the safe and efficient production of the working face [1][2][3]. The column has been service for a long time in the environment of high stress, high humidity and containing corrosive media such as sulfur and phosphorus [4].…”
Section: Introductionmentioning
confidence: 99%